Intra and Inter-Hemispheric Correlations of the Order/Chaos Fluctuation in the Brain Activity During a Motor Imagination Task - Diaz-Munoz, H (Elsevier B.V., 2018)
The objective of the present study was to explore the degree of synchrony manifested by the fluctuation of the order/chaos oscillation between different areas of the brain (frontal, temporal and occipital). We made this exploration during the execution of the mental visualization of a motor task consisting of performing a self-invented ordered sequence of body movements. The sample consisted in the EEG of 9 professional dancers recorded during the process of imagining the sequence of movements. To study the variation of the order/chaos activity and the synchronic relationship of this balance between different regions of the cerebral cortex, we estimated the Hurst exponent and used linear Spearman correlations to evaluate order/chaos fluctuations synchronicity. The results showed H>0.5 values in all the electrodes, showing a strong self-similar and persistent brain activity during the imagination process. In addition, high order/chaos fluctuation synchrony indexes were found for the inter-hemispheric frontal and occipital areas in all the subjects, but poor order/chaos synchrony between temporal areas. © 2018 The Authors. Published by Elsevier B.V.